(untitled) (International Journal of World Civilizations and Philosophical Studies, 2026)
In today’s increasingly complex psychological and spiritual landscape, there is an urgent need for integrative frameworks that address not only mental distress but also the deeper human search for meaning, purpose, and inner balance. This paper explores the inner self through three distinct yet potentially complementary approaches to healing: Cognitive Behavioral Therapy (CBT), Islamic Psychology, and a modern reflective model called the 3As Heart-Centered Framework, which includes Awareness, Awakening, and Action. CBT, rooted in Western clinical psychology, focuses on restructuring thought patterns to influence behavior and emotional well-being. Islamic Psychology, on the other hand, is based on a spiritually grounded epistemology that emphasizes the purification of the soul (tazkiyat al-nafs) and aligning the qalb (heart) with divine guidance. The 3As Framework integrates elements from both traditions, providing a practical, spiritually sensitive pathway that guides from deep self-awareness to spiritual awakening and ethically guided action. By examining the theoretical foundations and shared values of these models, the paper proposes a more holistic approach to inner healing—one that engages the intellect, nurtures the heart, and honors the spiritual dimension of human existence.